King David & Bathsheba Part 1 - Akinseye, Sola (Literamed Publications Nigeria Limited, 2009)
Join King David,the greatest king of Ancient Israel,as he takes a look back at his life.Relive a story of desire, evil schemes and intrigues in this simply told and well illustrated story.
Keywords: Christianity; Bible Stories; Religion